Textual errors in Serlo of Bayeux’s poem about the capture of Bayeux - Moreed Arbabzadah (Tabularia)
Current editions of Serlo of Bayeux’s poem about the capture of Bayeux in 1105 contain numerous errors. The most important editions are those of Wright and Brial; I therefore focus on their editions in this article. I provide an example of an error in the Latin text printed by Wright, which probably results from the incorrect interpretation of a gloss. I then turn to Brial’s editions and provide some examples of various types of error in his works. I then discuss errors common to Brial and Wright and propose solutions. Finally, I discuss an unsolved problem.